Peningkatan keunggulan bersaing wirausaha melalui pelatihan SDM dan kemampuan manajemen - Kurniawati, Kurniawati; Saputra, Ginanjar Wira (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Advances in digital technology today have brought significant changes in various aspects, especially in the batik industry business. As Indonesian assets, small and medium enterprises (SMEs) are economic drivers that can improve the regional economy. The development of SMEs today has spread beyond the presence of digital marketing. But can marketing be done can provide an advantage? Or is it even difficult to expand into new markets? This study tries to examine the factors that can affect competitive advantage in the SME industry in the city of Bandung. This type of research is quantitative using an explanatory approach. The results in this study indicate that the three independent variables studied are HR training and management ability to competitive advantage. The results show that HR training has an effect on the competitive advantage of SMEs in the city of Bandung. second, management ability has a positive effect on the competitive advantage of SMEs in the city of Bandung. and third, simultaneously HR training and management skills have a positive effect on the competitive advantage of SMEs in the city of Bandung. This research is expected to provide input to organizations, especially in the SME industry, so that they pay more attention to the quality of their human resources and develop their capabilities by providing training so that they can contribute to the organization in facing competition.